Bilateral Non-arteritic Anterior Ischaemic Optic Neuropathy as the Presentation of Systemic Amyloidosis. (2nd November 2017) - Kanaan, M. Z.; Lorenzi, A. R.; Thampy, N.; Pandit, R.; Dayan, Margaret
ABSTRACT: A 75-year-old hypertensive female with stable idiopathic intermediate uveitis presented with bilateral sequential optic neuropathy with optic disc swelling. The optic neuropathy in the first affected eye (right) was thought to be due to non-arteritic anterior ischaemic optic neuropathy (NAION). Asymptomatic left optic disc swelling was found at routine review 2 months later, and a diagnosis of giant cell arteritis (GCA) was sought. Temporal artery duplex ultrasound showed the "halo sign, " but a subsequent temporal artery biopsy showed light-chain (AL) amyloidosis with no signs of giant cell arteritis. In this case, bilateral sequential ischaemic optic neuropathy mimicking non-arteritic anterior ischaemic optic neuropathy was the presenting sign of systemic amyloidosis involving the temporal arteries.